Exogenous application of platelet-leukocyte gel during open subacromial decompression contributes to improved patient outcome. A prospective randomized double-blind study - Everts, P A; Devilee, R J J; Brown Mahoney, C; van Erp, A; Oosterbos, C J M; Stellenboom, M; Knape, J T A; van Zundert, A (European surgical research, 2008)
Platelet-leukocyte gel (PLG) is being used during various surgical procedures in an attempt to enhance the healing process. We studied the effects of PLG on postoperative recovery of patients undergoing open subacromial decompression (OSD). PLG was produced from platelet-leukocyte-rich plasma (P-LRP), prepared from a unit of whole blood. Forty patients were included in the study. Self-assessed evaluations, using the American Shoulder and Elbow Surgeons scoring system of activities of daily living (ADL), joint instability, pain levels, pain medications, and clinical evaluations for range of motion were conducted. Platelet and leukocyte counts were significantly increased in the P-LRP compared to baseline counts. Treated patients demonstrated decreased visual analog scales for pain and used significantly less pain medication, had an improved range of motion during passive forward elevation, external rotation, external rotation with arm at 90 degrees abduction, internal rotation, and cross body adduction compared to control patients (p < 0.001). No differences in the instability score were observed between the groups. Furthermore, treated patients performed more ADL (p < 0.05). In the PLG-treated group, recovery was faster and patients returned earlier to daily activities and also took less pain medication than control subjects.